2018
DOI: 10.14704/nq.2018.16.5.1243
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based English Teaching Module on the Administration of Electroencephalography-Based Neurofeedback Training for Chinese Students

Abstract: This paper aims to realize the administration of electroencephalography (EEG)-based neurofeedback (NFB) training for college English teaching and learning. For this purpose, a web-based NFB training system was developed, consisting of training devices, schedules, environment, operations and troubleshooting. Then, the system was applied to English teaching in a college. During the 10-week training period, the 19 participants received 20 sessions of NFB training, and filled out questionnaires before and after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…This may be because games are more interactive, fun, and exciting, especially for children. Zhang [107] also discussed measuring student concentration using web-application based on English vocabulary. The students need to understand the words and then click the word if it belongs to the animal category; in the study, the author showed a significant improvement in the small number of participants only in China.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because games are more interactive, fun, and exciting, especially for children. Zhang [107] also discussed measuring student concentration using web-application based on English vocabulary. The students need to understand the words and then click the word if it belongs to the animal category; in the study, the author showed a significant improvement in the small number of participants only in China.…”
Section: Discussionmentioning
confidence: 99%
“…The research focuses on individuals using prosthetic arms, gait exoskeletons, and state-of-the-art stroke rehabilitation for Lower/Upper extremities (UE/LE)). In this study, we place particular emphasis on recent technological advancements in Eating disorders [5], obesity [8], [11], drug addiction [12], [15], [16], alcohol addiction [19], [21], [22] assistive technology To help the rehabilitation of persons with physical disabilities.…”
Section: Research Processmentioning
confidence: 99%
“…Upper and lower extremities [7], [8], [11], persons with tetra-or quadriplegia [13], [18], [19], motor nerve control locked-in patients [11], [12], [13], [15], [61], [62], [36], [64] diagnosis To assist diagnosis through neurophysiological markers.…”
Section: Research Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptive technology refers to the enhanced versions of the existing tools that offer extra features and interaction opportunities to help people perform specific tasks [ 27 ], such as in education. Zhang [ 28 ] proved that students, particularly Chinese students, can better learn English using BCIs. Chiang et al [ 29 ] measured the attention level of students and concluded that they can become more focused and learn better using BCIs.…”
Section: Introductionmentioning
confidence: 99%